Price drift before U.S. macroeconomic news: private information about public announcements? - Alexander Kurov; Alessio Sancetta; Georg Strasser; Marketa Halova Wolfe (European Central Bank (ECB), 2016)
We examine stock index and Treasury futures markets around releases of U.S. macroeconomic announcements. Seven out of 21 market-moving announcements show evidence of substantial informed trading before the official release time. Prices begin to move in the " direction about 30 minutes before the release time. The pre-announcement price drift accounts on average for about half of the total price adjustment. These results imply that some traders have private information about macroeconomic fundamentals. The evidence suggests that the pre-announcement drift likely comes from a combination of information leakage and superior forecasting based on proprietary data collection and reprocessing of public information.
Keywords: E44; G14; G15; 330; drift; financial markets; informed trading; macroeconomic news announcements; pre-announcement effect